Design and Implementation of Improved High Step-Down DC-DC Converter for Electric Vehicles - Dong-Ryeol Park; Yong Kim (Energies, 2021)
An improved high step-down DC-DC converter for charging the batteries in an electric vehicle application is proposed in this paper. It adopts the topology of the conventional full-bridge converter, which has a coupled inductor current-doubler rectifier as the secondary side of the transformer. In addition, four power switches are driven using a phase-shifting technique. The proposed converter can achieve a high step-down voltage with low-voltage stress on the rectifier diodes. In addition, the coupled inductor current-doubler rectifier of the secondary side can reduce the ripple current and losses of the secondary side to achieve high efficiency. Furthermore, the proposed converter can overcome the drawbacks of the conventional full-bridge converter, such as switching loss caused by high switching frequency, duty-cycle loss, voltage stress, and numerous components, and can increase the efficiency with the soft-switching technique. A 600 W laboratory prototype of the proposed converter was manufactured. The results of the experiments performed with the prototype proved the effectiveness and validated the use of the proposed converter for better charging of electric vehicles.